Higher risk for chronic graft‐versus‐host disease (GvHD) in HLA‐G mismatched transplants following allogeneic hematopoietic stem cell transplantation: A retrospective study. (27th July 2022) - Neuchel, Christine; Gowdavally, Sowmya; Tsamadou, Chrysanthi; Platzbecker, Uwe; Sala, Elisa; Wagner‐Drouet, Eva; Valerius, Thomas; Kröger, Nicolaus; Wulf, Gerald; Einsele, Hermann; Thurner, Lorenz; Schaefer‐Eckart, Kerstin; et al.
Abstract : Introduction: Graft‐versus‐host disease (GvHD) is a major complication after allogeneic hematopoietic stem cell transplantation (allo‐HSCT) and is highly influenced by the degree of HLA matching between recipient and donor. The HLA‐class Ib molecule HLA‐G has been shown to promote tolerogenicity through its interaction with inhibitory receptors found on several immunocompetent cells. We hypothesized that in an allo‐HSCT setting, HLA‐G mismatches may negatively impact the HLA‐G‐mediated tolerogenicity either due to inefficient interaction with the inhibitory receptors of the transplanted immune cells or due to direct allorecognition of mismatched HLA‐G on host cells by the immune cells of the donor. Methods: In order to explore this hypothesis, we investigated the impact of HLA‐G mismatching in 2.083 10/10 matched high resolution HLA‐typed allo‐HSCT transplants. Results: We found that the risk of chronic GvHD was significantly higher in HLA‐G‐mismatched transplant cases as compared with the HLA‐G‐matched control group (HR: 1.46, 95%CI = 1.11–1.91, p  = 0.006). Sub‐analysis of the mismatch vector revealed that this effect was only detectable in the GvH (HR: 1.89, 95%CI 1.39–2.57, p  < 0.001) but not the HvG direction (HR: 1.01, 95%CI = 0.63–1.63, p  = 0.967). In addition, the negative impact of HLA‐G mismatching on chronic GvHD was only significant in younger patients (<30y HR: 3.02, 95%CI = 1.25–7.28, p  = 0.014; >29y HR: 1.28, 95%CI = 0.94–1.72, p  = 0.113). Discussion: Our results indicate that HLA‐G mismatches may contribute to the onset of chronic GvHD, especially in younger patients and should therefore be avoided when possible.